2008
DOI: 10.1590/s0100-879x2008005000024
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies in Brazilian hepatitis C virus carriers

Abstract: Hepatitis C, a worldwide viral infection, is an important health problem in Brazil. The virus causes chronic infection, provoking B lymphocyte dysfunction, as represented by cryoglobulinemia, non-organ-specific autoantibody production, and non-Hodgkin's lymphoma. The aim of this research was to screen for the presence of antiphospholipid autoantibodies in 109 Brazilian hepatitis C virus carriers without clinical history of antiphospholipid syndrome. Forty healthy individuals were used as the control group. IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Some studies, however, have found an increased incidence of thrombotic disorders in patients with chronic HCV with aPL. Atta et al [35] reported that chronic HCV patients have a significant production of aPL, mainly IgA anti-β2GPI antibodies, which are not associated with clinical manifestations of APS. Other studies have found no relationship between HCV and APS with no clinical manifestation of APS being found in aCL and HCVpositive patients before or during follow-up visits [36][37][38].…”
Section: Hepatitis C Viral Infection and Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Some studies, however, have found an increased incidence of thrombotic disorders in patients with chronic HCV with aPL. Atta et al [35] reported that chronic HCV patients have a significant production of aPL, mainly IgA anti-β2GPI antibodies, which are not associated with clinical manifestations of APS. Other studies have found no relationship between HCV and APS with no clinical manifestation of APS being found in aCL and HCVpositive patients before or during follow-up visits [36][37][38].…”
Section: Hepatitis C Viral Infection and Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Moreover, an association between viral hepatitis and aPL-related thrombotic complications has been also documented [19], suggesting that aPL may not only be an epiphenomenon of the infectious process but they may also play a pathogenic role. However, these data have been challenged in other studies [20,21]. In a previous meta-analysis [22], aCL were found to be significantly more frequent in both HBV-and HCV-infected patients compared to healthy controls (OR 13 and 14, respectively), whereas a trend towards a higher prevalence of anti-␤ 2 GPI -not achieving statistical significance -was found in HCV-infected, but not in HBV-infected subjects.…”
Section: Introductionmentioning
confidence: 90%
“…Twenty studies (28 data-sets) [15][16][17][18][19][20][21][27][28][29][30][31][32][33][34][35][36][37][38][39], for a total of 2319 cases and 1901 controls, evaluated aCL positivity in hepatitis patients and healthy controls. Hepatitis was found to be significantly associated with aCL positivity as compared to controls (OR: 11.38, 95% CI: 7.92-16.35; P < 0.00001, Fig.…”
Section: Acl Positivitymentioning
confidence: 99%
See 2 more Smart Citations